Perancangan UI/UX Untuk Situs Web Edukasi Memperkuat Respon Terhadap Perundungan: iqbal - Rohman, Iqbal Zabal (Pusmedia Group Indonesia, 2024)
The Independent Study Program in Web Development at PT Kinema Systrans Multimedia, supported by Infinite Learning and the Merdeka Belajar - Kampus Merdeka initiative by the Ministry of Education, Culture, Research, and Technology of Indonesia, is designed to sharpen students' skills in web development to meet the demands of Industry 4.0. The program offers an intensive curriculum that includes UI/UX design, frontend and backend development, and cybersecurity. Students also engage in micro-projects focusing on the issue of bullying, where they research and develop innovative web-based solutions to aid victims. This program not only enhances technical skills but also non-technical abilities such as public speaking and digital marketing, shaping well-rounded web developers and contributing to the resolution of social issues